TRANSFORMASI DAKWAH UMAR BIN KHATTAB: DARI PENENTANG MENJADI PILAR KEKUATAN ISLAM DALAM PERISTIWA HIJRAH - Fatwa, Khairunnisa; Shofiyah; Azila, Nur; Rayhana, Cindi; Rtonga, Nesa Fatma Melisa; Ujung, Nur Nisa Dwi Supari; Mahidh, Nadya Rahmatika Ghania; Windari, Sri (Cahaya Ilmu Bangsa Institute, 2025)
This study examines the transformation of Umar ibn Khattab's role from an early opponent of Islam to a significant pillar of strength in Islamic dakwah, particularly during the Hijrah. Employing a historical approach and literature analysis of hadiths, historical texts, and relevant interpretations, this research traces Umar's change in attitude, contributions, and courage in supporting the development of Islam. The findings reveal that Umar's conversion not only changed the course of his life but also strengthened the position of the Muslim community, making the Hijrah a crucial turning point in Islamic history. This transformation provided a new dimension to the early Islamic dakwah strategies and the establishment of a strong Muslim community.